PANCA WASTA TEACHINGS AS A SOURCE OF INSPIRATION CREATION FOR DHAPUR KRIS - Haris Fajar Nugroho; Dharsono Dharsono (ARTISTIC : International Journal of Creation and Innovation, 2021)
Panca Wasta is a teaching at the level of family life  which contains advice on values that elevate human position in personality, nobility, welfare and knowledge that must be possessed by a man (Javanese) in particular. The focus of the creation of the work is in the form of a kris blade which is inspired by the five elements of the Panca Wasta teachings which contain; wisma, turangga, kukila, curiga and wanita, using recycled metal. The purpose of the creation of this work is to create a dhapur kris blade using recycled metal with a metaphorical tinatah motif from the five elements of the panca wasta teachings. The creation of works uses an artistic creation approach, namely; experiment, contemplation and embodiment of works. The resulting work is a kris blade complete with warangka, hulu/jejeran/ukiran, mendhak, and pendok of Surakarta style. When the teachings of Panca Wasta are used as the concept of creating a kris, it shows that the work of a kris is quite interesting, has aesthetic beauty and full of philosophical values and meanings.